Ant communities (Hymenoptera: Formicidae) in an urban ecosystem near the Atlantic Rainforest - Kamura,CM. (2007)
The relationships between an urban ecosystem located near the Atlantic Rainforest in southeastern Brazil and ant communities were studied with the objective of quantifying the ant richness and abundance in the household environment and its surroundings. Eighty residences were sampled, where 58 species and 28 genera pertaining to 7 sub-families were found to be present. Inside the residences, the species richness was found to be lower (26), although the abundance was greater (10,670), with the wash area and kitchen being the locales that contributed with the greatest number of hits. The opposite was true in the areas outside the residences, where 54 species and 3,747 ants were observed. Inside houses, the species known as Tramp ants were found, in the following order of importance: Solenopsis -saevissima, Tapinoma melanocephalum, Linepithema humile, Paratrechina fulva, Wasmannia -auropunctata, P. -longicornis, Pheidole megacephala, Monomorium pharaonis and M. floricola. Externally, mainly in the yards and gardens, species such as Octostruma rugifera, Heteroponera dolo, Hypoponera sp.1 and sp.6, Gnamptogenys sp. 4, G. striatula, Odontomachus meinerti, Pachycondyla constricta and P. striata were found. In general, a greater number of species and lower abundance of individuals were observed in the neighborhoods nearer the mountains than in those closer to the urban center.